Voters perception on the performance of Selangor state government under Pakatan Rakyat coalition / Akmal Hisham Abdul Rahim - Abdul Rahim, Akmal Hisham (2013)
In any country which claimed to be a democratic country will hold the idea that politicians are responsible for their decisions during the tenure of their services and it is considered as the foundations of democracy. Thus, when a government benefits from good policy performance or when a government suffers from poor policy performance, it will be judged by the voters. The key assumptions are that the government are given credit for the positive changes and be blamed for any negative or failures in their performance. Thus, after four years Pakatan Rakyat formed the government in Selangor, are Selangor voters generally satisfied with the performance under the new government? Does the policy conducted by the Selangor Pakatan Rakyat government really concerned with the welfare of the people and accurately reaching its target or objective? This is an important question because any political parties which have inclination to govern Selangor state government will depend on the voters’ perception and satisfaction. Data were collected through questionnaires among registered voters which involved 560 respondents from 56 DUN in Selangor from 25th August 2012 until 30th September 2012. Based on the result from this study,majority of the voters are satisfied and have positive perception towards the current government performance. This research also found that the most influential factor for voters is economic performance. As for moderating effect, economic performance has a clear interaction with all ethnicity while other predictor such as local government matters to Indian only. From 5 hypotheses, all were accepted because each has a positive significant relationship. The findings concluded that voters in Selangor appear to be having a positive perception towards the current government but with the 13th Malaysian General Election is just around the comer, Selangor could be considered an open game for all political parties.